Examining Indonesian Teacher Roles in EFL Classroom: Insights from Elementary Teacher Narratives - Suryadi, Adi Irma; Nurkamto, Joko; Setyaningsih, Endang (FKIP Universitas Lampung, 2022)
Examining Indonesian Teacher Roles in EFL Classroom: Insights from Elementary Teacher Narratives. Objectives: Different roles have been attributed to teachers; from knowledge transmitter to caregiver. These roles are intertwined with one another and their complexity has attracted numerous researchers to investigate. In spite of the extensive literature and studies on teacher roles, very few studies have highlighted the complexity and changing roles of teachers from the insider point of view. This study explores the insider perspective of an elementary school teacher to gain clearer insights on teacher roles. Methods: The study focuses on how teachers narrate their roles as teachers and draw emerging themes from the narration. The data of this study were collected by semi-structured interviews, classroom observation, and document analysis. Findings: Through thematic analysis, the study reveals that the teacher played many roles from planning the materials, managing the class, monitoring and evaluating the students’ progress. Conclusion: These imply that teacher professional development and teacher competence become a concern in order to optimize the teachers’ roles. Keywords: Changing teachers’ roles; elementary school teachers’ roles; narrative inquiry.DOI: http://dx.doi.org/10.23960/jpp.v12.i1.202224